Teraz Poznań! O egzaminach państwowych z języka polskiego jako obcego - Węgrzak, Ewa; Wieczorek, Izabela (Wydawnictwo „Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The authors outline the history of state examinations for certification in Polish as a foreign language, focusing on their organization and structure in Poznań. In particular, the results of the Poznań-based examinations are compared with the average results of all exams carried out in Poland and abroad, proving that, basically, they do not differ much from one another. A detailed analysis of the results makes it also possible to formulate certain postulates related to the preparation for the examination with certification for the School of Polish Language and Culture for Foreign Students at Adam Mickiewicz University that may be taken into consideration in the future.
Keywords: certification; competence levels – B1, B2, C2; teaching of Polish as a foreign language; testing process; state examination; Poznań